Impact of ocean noise on mammalian life (case study: Samarinda waters) - Sri Ratih Deswati; Muhammad Syahrir; Mujiyanto Mujiyanto (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Noise pollution, or unwanted sounds in the ocean, can have a negative impact on marine mammals, especially on their biological behaviour when hunting for prey and changes in diving habits when leaving their habitat. This noise study was carried out in the waters of Samarinda with the help of a passive system acoustic instrument, which captures the range of sound intensity in the water column and supporting data in the form of sound range and activity above sea level. The sound range of 38.10-78.60 dB (A) above the water surface is safe for both everyday activities and as a habitat for mammals. Similarly, the underwater sound intensity between 0.84 and 138.47 dB re 1 Pa falls within this range. The noise condition in the study area is still expected. It can be used as an initial reference for the tolerance of sound intensity that applies to living things around the research location. The noise of the sea in Samarinda's waters has no effect on the lives of animals.Keywords:NoiseSound intensityMarine mammalHydrophoneSmartNoise